2003
DOI: 10.1046/j.1523-1747.2003.12040.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignancies in Psoriasis Patients Treated with Cyclosporine: a 5 y Cohort Study

Abstract: This prospective long-term cohort study investigated the incidence of malignancies in severe psoriasis patients treated with cyclosporine. A total of 1252 patients were followed prospectively for up to 5 y. Malignancies were recorded prospectively. Incidence rates for malignancies were compared with the general population using standardized incidence ratios. The effect of duration of exposure to cyclosporine and to previously administered anti-psoriatic treatments on the incidence of malignancies was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
267
4
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(285 citation statements)
references
References 26 publications
10
267
4
4
Order By: Relevance
“…In the available literature there is some evidence to suggest a relationship between psoriasis and cancerogenesis [1,2]. In our report the anti-androgen treatment caused the manifestation of psoriasis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the available literature there is some evidence to suggest a relationship between psoriasis and cancerogenesis [1,2]. In our report the anti-androgen treatment caused the manifestation of psoriasis.…”
Section: Discussionsupporting
confidence: 52%
“…Cutaneous manifestation is always a predominant clinical feature. However, several reports suggested that there might be a link between psoriasis and disorders of other organs, including malignancy [1,2]. The complex etiopathogenesis of psoriasis includes interaction of various genetic, environmental and immunological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high placebo response rate in patients with PsA (14), data from uncontrolled trials may be misleading. In addition, discontinuation rates due to lack of response and adverse events are typically high for conventional systemic therapies (38), and longterm safety is a concern (39,40). Two biologic agents, etanercept and infliximab, have recently been shown to be effective in the treatment of PsA, and these agents along with alefacept also reduce psoriasis symptoms (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…80,81,85 Additionally, treatment of psoriasis patients with cyclosporine and methotrexate has been associated with the development of lymphoma. [99][100][101] There is also concern that the biologic therapies used to treat psoriasis, which selectively target specific components of the immune system, might increase the risk of lymphoma in these patients.…”
Section: Malignanciesmentioning
confidence: 99%